Mesenchymal stem cell therapy in acute kidney injury (AKI): review and perspectives - Sávio-Silva,Christian (2020)
SUMMARY INTRODUCTION: Acute kidney injury (AKI) is highly prevalent today. It has a multifactorial aetiology and affects people of all ages, genders and ethnicities. Its treatment is essentially supportive of renal function substitution, so new treatment alternatives such as mesenchymal stem cell therapy (MSCs) should be investigated. METHODS: This review encompasses our understanding of the main mechanisms of action of MSCs in preclinical models of AKI by renal pedicle clamping ischemia-reperfusion, chemotherapy (cisplatin) and kidney transplantation in small and large animals, as well as outcomes in patients with AKI due to ischemia and kidney transplantation. RESULTS: Cellular therapy with MSCs has benefits in preclinical studies of AKI through various mechanisms, such as anti-inflammatory, antiapoptotic, oxidative anti-stress, antifibrotic, immunomodulatory and proangiogenic. In humans, MSC therapy is safe and effective. However, the challenges of MSC cell therapy include investigating protocols about the optimal dose of these cells, the route and frequency of appropriate administration, and the design of further biodistribution studies over a long follow-up period. In addition, a better understanding of molecular signalling and cellular interactions in the microenvironment of each organ and tissue is needed in order to define the best time to administer MSCs. Another challenge would be to mitigate the heterogeneity of the profile of cultured MSCs through preconditioning approaches. CONCLUSIONS: Cellular therapy with MSCs is very promising and should be part of the treatment of AKI patients in combination with other approaches already available, helping to accelerate recovery and/or slow the progression to chronic kidney disease. Randomized, multicentre controlled studies are needed to develop robust protocols that validate population-based cell therapy with MSCs.